Pengaruh Pertumbuhan Ekonomi dan Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan Perkotaan di Indonesia - Syefrina Silvia Mayani; Novya Zulva Riani (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This research aims to determine the influence of: (1) GDPR growth rate, (2) open unemployment rate, and (3) average length of schooling on urban poverty levels. This research uses secondary data with a quantitative type of panel data research, namely a combination of 2015-2022 time series data and cross section data from 34 provinces in Indonesia. This research uses the panel data regression method. The results of the regression analysis show that: (1) the rate of GRDP has a positive and significant effect on the level of urban poverty in Indonesia, (2) the level of open unemployment has a positive and significant effect on the level of urban poverty, and (3) the average number of years of schooling is over the age of 15 year has a significant negative effect on urban poverty levels in Indonesia.